Characterization of microinjection moulded composites of polyamide 6 and carbon nanotubes - Ferreira, Tânia (2012)
Microinjection molding is a powerful technology in micro-manufacture, providing millimeter scale parts at large scale production rate. In order to produce homogeneous composite parts, good dispersion of the nanoreinforcement in the polymer matrix is required. In the present work the carbon nanotube (CNT) reinforcement was dispersed in polyamide 6 (PA6) using a mini twin-screw extruder. Nanocomposites were prepared with different compositions (1% and 4,5%) of pure CNT (p-CNT) and functionalized CNT (f-CNT).